2001
DOI: 10.1029/2000gl012502
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric water vapor increases over the past half‐century

Abstract: Abstract. Ten data sets coveting the period 1954-2000 are analyzed to show a 1%/yr increase in stratospheric water vapor. The trend has persister for at least 45 years, hence is unl•ely the result of a single event, but rather indicative of long-term climate change. A long-term change in the transport ofwater vapor into the stratosphere is the most probable cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
302
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(316 citation statements)
references
References 27 publications
11
302
0
1
Order By: Relevance
“…The interest in middle atmospheric H 2 O was further intensified following observations made by Oltmans and Hofmann (1995) and after this by others (SPARC, 2000, and references therein;Rosenlof et al, 2001) who found increasing H 2 O concentrations of 30-150 nmol/mol yr −1 in the middle atmosphere since 1954. Not only the possible causes of this trend but also the consequences for Earth's climate and the chemistry of the middle atmosphere are a matter of vital discussion Shine, 1999, 2002;Kirk-Davidoff et al, 1999;Stenke and Grewe, 2004;Röckmann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The interest in middle atmospheric H 2 O was further intensified following observations made by Oltmans and Hofmann (1995) and after this by others (SPARC, 2000, and references therein;Rosenlof et al, 2001) who found increasing H 2 O concentrations of 30-150 nmol/mol yr −1 in the middle atmosphere since 1954. Not only the possible causes of this trend but also the consequences for Earth's climate and the chemistry of the middle atmosphere are a matter of vital discussion Shine, 1999, 2002;Kirk-Davidoff et al, 1999;Stenke and Grewe, 2004;Röckmann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, early observations by Guo et al (1989) showed increasing δ 18 O(H 2 O) values from (80 ± 140)‰ at 22 km altitude to (400 ± 250)‰ at 37 km. Using a balloon-borne spectrometer, Johnson et al (2001) obtained low isotope ratios of -(300-30)‰ (average: -128‰) for δ 18 O(H 2 O), and of -(400-0)‰ (average: -84‰) for δ 17 O(H 2 O) at 12-20 km altitude.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been motivated by observations which show a positive trend during the late twentieth century (e.g. Rosenlof et al, 2001;Scherer et al, 2008) and a sudden decrease of around 10% (∼0.5 ppmv)…”
Section: Introductionmentioning
confidence: 99%